Response of Pulgher Hajj and Umrah: Arabic Language as a Practical Communication: Respon Jamaah Haji dan Umrah: Bahasa Arab sebagai Bekal Komunikasi Praktis - Khizanatul Hikmah; Muhlasin Amrullah; Farikh Marzuki Ammar; Silviya Yuliyanti (Academia Open, 2023)
Language is a communicative phenomenon in a social context so that the ability to speak Arabic is no longer a complement but a vital requirement that must be mastered by prospective haj and umrah pilgrims. Therefore, the focus of research conducted by researchers is on user response to the design of a traveling-based communicative Arabic language e-book for Hajj and Umrah pilgrims at KBIH Jabal Nur Sidoarjo. This study used a descriptive qualitative method approach with data collection techniques including observation, documentation, and questionnaires and data analysis techniques with Miles and Huberman's interactive analysis model. The results showed a percentage of 90.8%, meaning that most of the congregation stated that the traveling-based communicative Arabic ebook included a new design typology that could be used as a guide in communicating practical Arabic in Saudi Arabia. Highlights: Vital Language Skill: Proficiency in Arabic becomes essential for Hajj and Umrah pilgrims due to the communicative nature of these journeys. Innovative Design: The study focuses on a new design typology for a traveling-based communicative Arabic e-book. Positive Reception: Research findings reveal a 90.8% approval rate among participants, indicating the effectiveness of the e-book for practical Arabic communication in Saudi Arabia. Keywords: Response, Hajj and Umrah, Arabic, communication.